CARICOM at 40 : investing in the future (Newsdesk Media LondonGB, 2014)
Focuses on the many and varied investment opportunities that the Region offers. Celebrates the culture, heritage and history of our Community. Profiles the 15 CARICOM Member and Associate Member States including the economic climate of strengths of each Member. Provides contact details for investment agencies and ohter relevant information to aid investment decisions.l
Keywords: INVESTMENT